Csr Sebagai Salah Satu Faktor Yang Berpengaruh Terhadap Return Saham - Anggraini, Dewi (Jurnal Akuntansi, 2014)
This Research Examines The Influence Of Csr Implementation Towards Stock Return In The Companies That Are Listed In Kompas-100 Index.